Clinical and Radiographic Diagnosis of Coronal Shear Fractures of the Metacarpal Head in Adolescents: A Case Series - Darryl Ee Ming CHEW; Tomasz Jakub MERTA; Dawn Sinn Yii CHIA (The Journal of Hand Surgery (Asian-Pacific Volume), 2026)
Intra-articular coronal shear fractures of the metacarpal head in adolescents are rare and easily overlooked because the fracture plane lies parallel to standard radiographic projections. We describe four adolescent patients to define distinct clinical and radiographic diagnostic clues that support early recognition. A consistent injury pattern of axial loading across a hyperextended metacarpophalangeal joint was observed. Two patients demonstrated a reproducible mechanical click occurring during terminal hyperextension. Initial radiographs were subtle or equivocal in three patients, with metacarpal head squaring and a double shadow sign representing key radiographic signs of coronal fracture morphology. Computed tomography clarified fracture morphology when plain radiographs were inconclusive and demonstrated intra-articular incongruity requiring operative treatment. Delayed recognition in one patient resulted in symptomatic malunion. Awareness of the characteristic diagnostic clues should prompt advanced imaging and facilitate earlier identification of this uncommon intra-articular injury. Level of Evidence: Level V (Therapeutic)